A Cyclam‐Based Fluorescent Ligand as a Molecular Beacon for Cu2+ and H2S Detection. Issue 33 (7th September 2017) - Mirra, Silvia; Strianese, Maria; Pellecchia, Claudio
Abstract : A pentadentate cage‐like cyclam‐based fluorescent ligand has been designed, synthesized, and characterized by 1D and 2D NMR spectroscopic analysis. To further characterize the title ligand, ESI‐MS, UV/Vis spectroscopy, and fluorescence experiments have been also performed. Its suitability as a chemosensor for the detection of Cu 2+ ions has been successfully explored with a variety of spectroscopic techniques (i.e., ESI‐MS, UV/Vis, and fluorescence). A Job's plot experiment, together with ESI‐MS experiments, indicate a 1:1 stoichiometry for the binding of Cu 2+ to the cyclam‐based ligand. Fluorescence experiments corroborate this hypothesis. The resulting system is selective in the recognition of copper and is stable for a week, as assessed by fluorescence spectroscopy. The Cu II complex has been isolated and tested as a fluorescent probe for the detection of H2 S. NMR spectroscopy and ESI‐MS investigations have provided evidence that H2 S recognition occurs through a copper‐displacement mechanism, as reported in the literature for different copper complexes. The system functions with a selective response to HS –, harnessing a concentration‐dependent "turn‐on" of the initial fluorescence intensity. Abstract : A pentadentate cage‐like cyclam‐based fluorescent ligand has been designed, synthesized, and characterized by a variety of spectroscopic techniques. The suitability of the title ligand for the detection of Cu 2+ ions, and that of the corresponding copper complex for the detection of H2 S, have been successfully explored.